Studies on microsporidian infection in Parapenaeopsis stylifera - Jose, Jasmine K (Indian Journal of Fisheries, 2011)
Parapenaeopsis stylifera, infected with microsporidians showed a distinct whitishdiscolouration in their abdominal musculature. Histopathological and histochemicalstudies of the infected tissues revealed the presence of microsporidian sporesin different stages of development and accumulation of iron respectively